Prueba piloto en la eficacia de la técnica de distracción contingente con material audiovisual en pacientes de 4 a 6 años durante la atención odontológica en la universidad Antonio Nariño (2020)
The present study was aimed at determining the efficacy of the use of contingent distraction in the care of children with difficult management at the time of consultation at ages between four and six years attending the dental clinic of the Universidad Antonio Nariño. For this, a research with a quantitative and quasi-experimental approach was carried out, taking as a sample 20 patients, between 4 and 6 years of age, from the dental clinic of the Universidad Antonio Nariño, based in Villavicencio, although to answer the two surveys, we counted with the collaboration of the parents or companions of the study population. The study began with establishing the Frankl scale in which patients from 4 to 6 years of age are at the beginning of the study, for which the initial survey was consulted, whose data also served to characterize the population subject of study. Subsequently, the application of the contingent distraction management technique was continued with audiovisual material before, during and after dental care. In the end, the efficacy of the applied contingent audiovisual technique was evaluated, with the Frankl scale, showing the benefits of this, being a good option for pediatric dentistry care.